Food technology - Morris, Neil, 1946- (Chicago : Raintree, 2012)
Explores how science and technology are used to create, preserve, and distribute the foods people eat, as well as make them safer.
"Revealed"--Cover.
Includes bibliographical references (p. 46) and index.
6.5
5-8
5-8
Keywords: Food industry and trade -- Juvenile literature; Nutrition -- Juvenile literature; Food industry and trade; Nutrition; Food industry; Nutrition